PENDEKATAN BUDAYA DALAM PEMBINAAN GURU: PEMBINAAN GURU OLEH KEPALA SEKOLAH DASAR DI YOGYAKARTA - ., Mundilarno (Jurnal Cakrawala Pendidikan, 2005)
The qualified education has an important role in developing the human resources. The highly strategic role ofthe teacher improve the quality ofeducation is questionable. One ofthe causal factors ofthe gap between the expected and observed quality ofeducation is the low ofquality ofthe teacher. The unexpected, current quality ofthe teacher is commonly believed to be caused by the negligence in respect ofthe strategic cultures values ofthe teacher. According to this condition, the main problem ofthis research is the Javanese culture approach in the elementary educational supervi sion in Special Province ofYogyakarta. This research was aimed at finding out concepts ofJavanese cultural approach implemented by the elementary school principals in educational superVision. The re search used a qualitative-naturalistic approach covering description and analysis ofthe supervisory processes, the opinions and expecta tions ofthe teachers and supervisory, family members, and public figures. The research findings showed thatkaprawiran and kaprayitnan (heroism and cautiousness) values were used in educational supervi sory. In Javanese culture, the principals must always give examples, motivations, and supervision ("ing ngarso sung tulodo, ing madya mangun karso, IUt wuri handayani "). The principals must also be patient, discipline, and implement the "Hasta Bratd’ (eight principles ofthe Javanese culture in supervision). Theeducational supervision was expected to use an "achievement oriented without creating distrubances approach" ("kena iwake ora buthek banyune").As the implication of the research findings, the Javanese approach in e1ementaIy educational supervision may be relevant to be used in the other educational super vision and personel development programs and ingovemmentaJ institu tions in Yogyakarta, Central Java, East Java, and other provinces that have values closely related to Javanese culture. Key words: Quality o/teacher, heroism, cautiousness, example, andachievement without distrubances.